2020
DOI: 10.1101/2020.03.18.996660
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Variability within rare cell states enables multiple paths towards drug resistance

Abstract: Molecular differences between individual cells can lead to dramatic differences in cell fate following an applied treatment, such as the difference between death versus survival of cancer cells upon receiving anti-cancer drugs. However, current strategies to retrospectively identify the cells that give rise to distinct rare behaviors and determine their distinguishing molecular characteristics remain limited. Here we describe Rewind, a methodology that combines genetic barcoding with an RNA-based readout to di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 47 publications
1
20
0
Order By: Relevance
“…We applied this technique to BRAF-mutant melanoma cells in which a rare subpopulation of cells are resistant to BRAF inhibitors. We transduced WM989 melanoma cells with a high-complexity viral barcode library consisting of a transcribed 100 base pair semi-random barcode seq ence in he 3 UTR of GFP (Emert et al 2021) (Fig. 1C).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We applied this technique to BRAF-mutant melanoma cells in which a rare subpopulation of cells are resistant to BRAF inhibitors. We transduced WM989 melanoma cells with a high-complexity viral barcode library consisting of a transcribed 100 base pair semi-random barcode seq ence in he 3 UTR of GFP (Emert et al 2021) (Fig. 1C).…”
Section: Resultsmentioning
confidence: 99%
“…In these examples, the cellular state underlying the phenotype is stable enough to persist through multiple cell divisions, but is ultimately not permanent, and thus amenable to switching states. For cancer therapy resistance, drug-naive cells seemingly randomly fluctuate between two states, one which is susceptible to targeted therapy and another which would become resistant if he dr g is applied, ermed primed for dr g resis ance (Emert et al 2021;Shaffer et al 2017). However, the molecular drivers underlying these heritable, but reversible, memory states remain unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proposed, and experimentally shown, that transcriptional fluctuations within complex regulatory networks can result in a clonal population existing in multiple phenotypic states 9,10,42 . In cancer cells, such fluctuations can cause cells to switch between drug-sensitive and drug-resistant states 43 in a manner that can be perturbed by targeting key transcription factors 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Raj showed that cells contain cryptic variability that only becomes apparent after a perturbation, like drug exposure. 64 Raj also presented unpublished data characterizing morphology, transcriptome, and phenotype across resistant cell colonies to classify resistant cells into different subtypes. Raj hopes that understanding how cells are primed for different fates will be applicable across a range of biological processes, including stem cell differentiation and induced pluripotent stem cell reprogramming.…”
Section: Computational Approachesmentioning
confidence: 99%